Microbial supernatants from Mobiluncus mulieris, a bacteria strongly associated with spontaneous preterm birth, disrupts the cervical epithelial barrier through inflammatory and miRNA mediated mechanisms. (February 2020) - Dude, Carolynn M.; Saylany, Anissa; Brown, Amy; Elovitz, Michal; Anton, Lauren
Abstract: Recent human clinical studies have identified Mobiluncus mulieris, a fastidious strict anaerobic bacterium present in the cervicovaginal (CV) space, as being strongly associated with spontaneous preterm birth (sPTB). However, the molecular mechanisms that underlie this association remain unknown. As disruption of the cervical epithelial barrier has been shown to contribute to the premature cervical remodeling that precedes sPTB, we hypothesize that M. mulieris, a microbe strongly associated with sPTB in humans, has the ability to alter cervical epithelial function. We investigated if bacteria-free supernatants of M. mulieris were able to disrupt the cervical epithelial barrier through immunological and epigenetic based mechanisms in an in vitro model system. Ectocervical cells were treated with supernatant from cultured M. mulieris and epithelial cell permeability, immune cytokines and microRNAs (miRNAs) were investigated. M. mulieris supernatant significantly increased cell permeability and the expression of two inflammatory mediators associated with cervical epithelial breakdown, IL-6 and IL-8. Moreover, treatment of the ectocervical cells with the M. mulieris supernatant also increased the expression of miRNAs that have been associated with either sPTB or a shorter gestational length in humans. Collectively, these results suggest that M. mulieris induces molecular and functional changes in the cervical epithelial barrier thought to contribute to the pathogenesis of sPTB, which allows us to hypothesize that targeting CV bacteria such as M. mulieris could provide a therapeutic opportunity to reduce sPTB rates. Highlights: Treatment of cervical cells with Mobiluncus supernatant increases cell permeability. Mobiluncus supernatant increases the expression of inflammatory markers IL-6 and -8 by cultured cervical epithelial cells. Mobilincus supernatant alters the expression of select miRNAs by cultured cervical epithelial cells.